Epistaxis Associated with Theileriosis and its Management in a Buffalo - A Case Report - Prajapati, Ankit S; Parmar, Jignesh J; Chauhan, Vandip D; Shah, Aditya I; Parikh, Pinesh V (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
that cause bovine theileriosis, are spread by ticks Hyalomma and Rhipicephalus, respectively. Bovine theileriosis results in severe livestock losses as well as financial losses on a global scale (Sharma et al., 2017). Apart from bovine, sheep and goats are also affected by this condition (Prajapati et al.